Nitrato orgânico 2-nitrato-1,3-dibutoxipropano (NDBP) atenua o estresse oxidativo e a hipertensão arterial mediada por angiotensina II via produção de óxido nítrico em animais experimentais - Porpino, Suênia Karla Pacheco (2016)
Background: Nitric oxide (NO) donors can act in the control and treatment of various cardiovascular complications, such as hypertension. In particular, an organic nitrate, 2-nitrate-1,3-dibutoxipropane (NDBP) developed in recent years by UFPB has shown great therapeutic potential. However, its mechanisms are not fully clarified. Aim: To investigate the effects and mechanisms of NDBP, elucidating their therapeutic potential in angiotensin II-mediated hypertension. Methods: In the first stage of the study, were performed in vitro experiments in normotensives Wistar rats (n=11) tissues for characterization of compound about ability to release NO by direct measurement of NO; and modulation of NADPH oxidase activity, by chemiluminescence technique. In the second stage of the study, in vivo experiments in C57BL / 6J mice (n=24), divided in four groups (control, NDBP, Ang II and Ang II + NDBP) were performed to investigate the therapeutic potential of NDBP in angiotensin II-mediated hypertension. The animals had implantation of osmotic minipumps containing Ang II (400 mg / kg / 24h) and after 9 days were treated with NDBP (40 mg / kg / day; ip). Blood pressure (BP) was measured by tail-cuff. At the end of the experiments, the animals were euthanized and blood and tissues were collected for analysis. Histopathological analyzes were performed using staining picrosirius. Superoxide levels were measured by NADPH oxidase activity via chemiluminescence and DHE fluorescence (5 mmol • L-1). Levels of serum nitrate/nitrite and cGMP were performed using specific kits. NADPH oxidase subunit expression were analyzed by real time qPCR. Putative antioxidant activity was determined by autoxidation with pyrogallol. Results: In vitro experiments revealed a dose-dependent increase in NO production mediated by NDBP in liver and kidney tissues, which was attenuated by the xanthine oxidase inhibitor febuxostat. In addition, the NDBP reduced NADPH oxidase activity and prevented its activation induced by ANG II. In vivo experiments showed that NDBP prevents the increase in hypertension in mice with chronic infusion of ANG II. This results were associated to the attenuation of cardiac hypertrophy, renal fibrosis, and reduced NADPH oxidase-derived oxidative stress in the kidneys, the heart, and liver. Furthermore, NDBP also increased plasma levels of nitrite and nitrate. On the other hand, the autoxidation with pyrogallol revealed that NDBP does not act as a direct antioxidant, justifying its involvement in the modulation of NADPH oxidase. Conclusions: The organic nitrate NDBP prevents the progression of angiotensin II-mediated hypertension. Regarding the mechanisms, our findings suggest that NDBP treatment is associated with sustained NO release and attenuated activity of NADPH oxidase, which requires functional xanthine oxidase.